(5/3)+(-1/2)-(-2/3)=
(-3/4)-(-1/2)+91/5)-(+2/3)=
(5/3)+(-1/2)+(1/5)-(+2/3)=
Soluções para a tarefa
Respondido por
14
Olá!
Para fazer estas questões necessita-se fazer o MMC!
(5/3)+(-1/2)-(-2/3)=
o MMC de 3,3 e 2 é 6!
6/3=2 -> 2*5 = 10
6/2=3 _> 3*(-1)=-3
6/3=2 -> 2*(-2)=-4
10+(-3)-(-4) / 6 = 11/6
-----------------------------------------------------
(-3/4)-(-1/2)+91/5)-(+2/3)=
o MMC dá 60!
-45-(-30)+1092-40 / 60= 1037/60
----------------------------------------------------
(5/3)+(-1/2)+(1/5)-(+2/3)= 21/30
Para fazer estas questões necessita-se fazer o MMC!
(5/3)+(-1/2)-(-2/3)=
o MMC de 3,3 e 2 é 6!
6/3=2 -> 2*5 = 10
6/2=3 _> 3*(-1)=-3
6/3=2 -> 2*(-2)=-4
10+(-3)-(-4) / 6 = 11/6
-----------------------------------------------------
(-3/4)-(-1/2)+91/5)-(+2/3)=
o MMC dá 60!
-45-(-30)+1092-40 / 60= 1037/60
----------------------------------------------------
(5/3)+(-1/2)+(1/5)-(+2/3)= 21/30
Perguntas interessantes
Português,
11 meses atrás
Matemática,
11 meses atrás
Administração,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás